Sex Differences in Outcomes among Stroke Survivors with Non-Valvular Atrial Fibrillation in China - Hong, Yan; Yang, Xun; Zhao, Wenjuan; Zhang, Xianghui; Zhao, Junli; Yang, Yuanju; Ning, Xianjia; Wang, Jinghua; An, Zhongping (Frontiers in Neurology, 2017)
Atrial fibrillation significantly increases the risk of stroke and disease burden and is an established predictor of poor outcomes after stroke. However, data regarding sex differences in long-term outcomes following stroke in patients with atrial fibrillation are scarce. We thus aimed to assess these differences. We recruited 951 consecutive patients with acute ischemic stroke and nonvalvular atrial fibrillation treated at three hospitals in Tianjin, China, from January 2006 to September 2014. Information regarding stroke subtype, severity, risk factors, and outcomes (mortality, dependency, and recurrence) at 3, 12, and 36 months after stroke was recorded. The prevalence of nonvalvular atrial fibrillation was 8.4% overall, with a higher frequency in women than in men (11.3% vs. 6.9%, P < 0.001). Among patients with nonvalvular atrial fibrillation, women were older than men. Women were more likely than men to have severe stroke (38.8% vs. 29.5%, P < 0.001), high levels of total cholesterol and high- and low-density lipoprotein cholesterol (all P < 0.001), hypertension (69.1% vs. 61.2%, P = 0.012), dyslipidemia (30.4% vs. 17.4%, P = 0.001), and obesity (18.5% vs. 11.6%, P = 0.003); they were less likely than men to be current smokers (12.2% vs. 33.6%, P < 0.001) and to consume alcohol (0.9% vs. 13.9%, P < 0.001). There were greater risks of dependency and recurrence at 36 months after stroke in women than in men (OR [95% CI], 1.64 [1.02–2.64] for dependency, P=0.043; and 2.03 [1.28–3.20] for recurrence, P=0.002) after adjustment for stroke subtype, severity, and risk factors. These findings suggest that it is crucial to emphasize the need for individualized stroke prevention education and promotion of healthy lifestyles in order to improve nonvalvular atrial fibrillation-related stroke outcomes and reduce disease burden in women.